2016
DOI: 10.1075/bpa.2.02tit
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 1. Bilingualism, executive control, and eye movement measures of reading

Abstract: This chapter selectively reviews the literature on bilingual language processing, with a special focus on the link to executive control, eye movements during reading, and differences between two different groups that are often lumped together: bilinguals (i.e., individuals who know two languages) and multilinguals (i.e., individuals who know more than two languages). To this end, we first discuss ideas about the cognitive demands associated with knowing more than a single language. We then review how eye movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 167 publications
0
11
0
Order By: Relevance
“…Second pass reading time was calculated by subtracting gaze duration from total reading time, or the total amount of time spent in a region. In turn, second pass reading time reflects additional processing of a region, particularly with respect to sentence- or discourse-level factors (for a review of eye-tracking measures, see Titone et al, 2016). Of note, in cases where participants only fixated the regions of interest on the first pass, the second pass time would be 0, and this would be included in the analysis.…”
Section: Methods Common To Experiments 1 Andmentioning
confidence: 99%
“…Second pass reading time was calculated by subtracting gaze duration from total reading time, or the total amount of time spent in a region. In turn, second pass reading time reflects additional processing of a region, particularly with respect to sentence- or discourse-level factors (for a review of eye-tracking measures, see Titone et al, 2016). Of note, in cases where participants only fixated the regions of interest on the first pass, the second pass time would be 0, and this would be included in the analysis.…”
Section: Methods Common To Experiments 1 Andmentioning
confidence: 99%
“…Lexical entrenchment can be assessed through the word frequency effect, which reflects how easily a word can be identified. The standard finding is that high-frequency words (e.g., home ) are recognized more easily and more rapidly than low-frequency words (e.g., kelp ); this finding is indexed by more skipping, shorter fixations, and fewer regressions in the eye movement record (reviewed in Rayner, 1998, 2009; Rayner, Pollatsek, Ashby & Clifton, 2012; Titone et al, 2016; Whitford et al, 2016). Word frequency effects are often regarded as a signature of lexical access, and reflect important structural properties of the mental lexicon (Rayner, 1998, 2009).…”
Section: Lexical Entrenchment Studies Of Bilingual Word Recognitionmentioning
confidence: 99%
“…Words with between-language lexical overlap include cognates , which share both orthography and semantics across languages (e.g., < piano> is an instrument in both English and French), and interlingual homographs , which share orthography, but not semantics across languages (e.g., < chat> is a conversation in English vs. cat in French). Studies involving both eye movement recordings and response-based tasks have generally reported facilitatory effects for cognates, and inhibitory effects for interlingual homographs (reviewed in de Groot, 2011; Kroll et al, 2016; Titone et al, 2016; Van Assche et al, 2012; Whitford et al, 2016).…”
Section: Cross-language Activation Studies Of Bilingual Word Recognitionmentioning
confidence: 99%
See 2 more Smart Citations